Sex Differences in the Neural Correlates of Specific and General Autobiographical Memory - Compère, Laurie; Sperduti, Marco; Gallarda, Thierry; Anssens, Adèle; Lion, Stéphanie; Delhommeau, Marion; Martinelli, Pénélope; Devauchelle, Anne-Dominique; Oppenheim, Catherine; Piolino, Pascale (Frontiers in Human Neuroscience, 2016)
Autobiographical memory (AM) underlies the formation and temporal continuity over time of personal identity. The few studies on sex-related differences in AM suggest that men and women adopt different cognitive or emotional strategies when retrieving AMs. However, none of the previous works has taken into account the distinction between episodic autobiographical memory (EAM), consisting in the retrieval of specific events by means of mental time travel, and semantic autobiographical memory (SAM), which stores general personal events. Thus, it remains unclear whether differences in these strategies depend on the nature of the memory content to be retrieved. In the present study we employed functional MRI to examine brain activity underlying potential sex differences in EAM and SAM retrieval focusing on the differences in strategies related to the emotional aspects of memories while controlling for basic cognitive strategies. On the behavioral level, there was no significant sex difference in memory performances or subjective feature ratings of either type of AM. Activations common to men and women during AM retrieval were observed in a typical bilateral network comprising medial and lateral temporal regions, precuneus, occipital cortex as well as prefrontal cortex. Contrast analyses revealed that there was no difference between men and women in the EAM condition. In the SAM condition, women showed an increased activity, compared to men, in the dorsal anterior cingulate cortex, inferior parietal and precentral gyrus. Overall, these findings suggest that differential neural activations reflect sex-specific strategies related to emotional aspects of AMs, particularly regarding SAM. We propose that this pattern of activation during SAM retrieval reflects the cognitive cost linked to emotion regulation strategies recruited by women compared to men. These sex-related differences have interesting implications for understanding psychiatric disorders with differential sex prevalence and in which one of key features is overgenerality in AM.